2000
DOI: 10.1103/physrevc.62.055203
|View full text |Cite
|
Sign up to set email alerts
|

High-statistics measurements of thep¯pΛ¯

Abstract: We report on precision measurements of the cross sections for the reactions p p→⌳ ⌳, p p→⌳ ⌺ 0 , and p p→⌺ 0 ⌳ in the region below 5 MeV excess kinetic energy above reaction threshold. For the p p→⌳ ⌳ measurement, the data represent a third and definitive scan through the threshold region by this experiment. Improvements in the detector system and analysis techniques, coupled with greatly increased statistics, have negated the question of the existence of a near-threshold resonance as had been indicated in our… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
1

Year Published

2002
2002
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 14 publications
1
15
1
Order By: Relevance
“…However, more recent studies, reported for instance at the LEAP98 Conference [339], indicated a smooth behaviour of the cross-section in this energy range. The nal analysis of the low-energy region [340] conrmed this result, as can be clearly seen in Fig. 4.…”
Section: Two-spin Correlation Datasupporting
confidence: 59%
“…However, more recent studies, reported for instance at the LEAP98 Conference [339], indicated a smooth behaviour of the cross-section in this energy range. The nal analysis of the low-energy region [340] conrmed this result, as can be clearly seen in Fig. 4.…”
Section: Two-spin Correlation Datasupporting
confidence: 59%
“…Interestingly, initial data forpp →ΛΛ suggested that there could be a near threshold resonance in the 3 S 1Λ Λ state [43]. However, a later high-statistics measurement by Barnes et al [27] ruled that out convincingly. This experiment scrutinized the first 5 MeV above theΛΛ threshold with an unprecedented resolution of 0.2 MeV.…”
Section: Resultsmentioning
confidence: 99%
“…Indeed, the only constraints we have for theΛΛ force come from the FSI in the reactionpp →ΛΛ. This reaction has been thoroughly studies in the PS185 experiment and data are available for total and differential cross-sections but also for polarization (P) and spin-correlation parameters (C i j ) [26,27,29], down to energies very close to the reaction threshold, see also the review in Ref. [28].…”
Section: Theλλ Interactionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been studied theoretically with two types of models: meson exchange or quark-gluon interactions. The first two generations of experiments [1] by PS185 were carried out at LEAR, the Low Energy Antiproton Ring at CERN, using unpolarized targets. The resulting cross sections and spin observables were described equally well by either theory.…”
Section: Introductionmentioning
confidence: 99%